The Two Dimensions of Narcissistic Personality and Support for the Radical Right: The Role of Right–Wing Authoritarianism, Social Dominance Orientation and Anti–Immigrant Sentiment. Issue 1 (January 2020) - Mayer, Sabrina J.; Berning, Carl C.; Johann, David
This paper offers an explanation of the link between grandiose narcissism and support for radical right parties. Drawing on representative data of the GESIS Panel ( N = 2827), focusing on support for the German radical right populist party Alternative for Germany in 2016 and treating grandiose narcissism as a two–dimensional concept, it is shown that the effects of grandiose narcissism are indirect rather than direct. The paper also reveals that it is mainly narcissistic rivalry that accounts for radical right party support, whereas narcissistic admiration has a protecting relationship. Finally, our results indicate that the indirect effects of narcissistic rivalry on radical right party support via right–wing authoritarianism and social dominance orientation, respectively, are mediated by anti–immigrant sentiment. All in all, our results suggest that in studies on ideological orientations and voting behaviour, both dimensions of grandiose narcissism should be considered due to their contradictory relationship. Moreover, our findings indicate that the success of radical right parties might be the expression of personality dispositions of some parts of the electorate. © 2020 The Authors. European Journal of Personality published by John Wiley & Sons Ltd on behalf of European Association of Personality Psychology